Supported Education: A Scoping Review - Brumer , Naomi Davids-; Kirsh , Bonnie (International Journal of Psychosocial Rehabilitation, 2018)
Background: The onset of mental illness is commonly between the ages of 16-25, affecting students in the midst of their educational pathways. The challenges faced by these students result in an increase in abandoned educational goals compared with their well peers. These challenges led to the development of supported educa- tion (SEd); however, there has been no comprehensive review of this intervention to date.Purpose: This study aims to determine how the literature conceptualizes and operationalizes the term “supported education”.Meth- od: This scoping review used the framework developed by Arksey and O’Malley. Eight databases were searched for the terms “supported education” and “supportive education” in titles, abstracts, and keywords.Findings: Supported education has defining characteristics, underlying theories, service delivery models, and interventions. Interpretation & Discussion: Although the need for SEd is clear, more work is needed to develop a universally accepted service delivery practice, with national policies to support its implementation.